Rethinking neoliberalism resisting the disciplinary regime - Schram, Sanford; Pavlovskaya, Marianna (Routledge, Taylor & Francis Group, 2018)
Neoliberalism remains a flashpoint for political contestation around the world. Written in a clear and accessible style, Rethinking Neoliberalism is a sophisticated synthesis of theory and practice, making it a compelling read for students of Political Science, Public Policy, Sociology, Geography, Urban Planning, Social Work and related fields, at both the advanced undergraduate and graduate levels.